The story of De Stijl Mondrian to Van Doesburg - Janssen, Hans 1954-; White, Michael 1969- (Abrams, 2011)
De Stijl is by far the most easily recognisable of all European avant-gardes. The radically geometrical construction and the cheery colourfulness of the art of Mondrian, Van Doesburg, Gerrit Rietveld, Bart van der Leck and their companions have become a trademark. This book brings it back to life with many historical documents, photographs, anecdotes and newspaper clippings that make clear the importance and influence of the Dutch movement.